Evaluating the Potential of ChatGPT as a Supplementary Intelligent Virtual Assistant in Periodontology - Bhawna Shyamsukha; Hiroj Bagde; Aniket Sharan; Megha Choudhary; Aishwarya Duble; Aadarsh V. Dhan (Journal of Pharmacy and Bioallied Sciences, 2025)
Introduction: In many fields, Artificial Intelligence (AI) has brought about paradigm change by enabling computer systems to do activities that were previously limited to human participation. Objectives: The study’s primary focus is to evaluate responses generated through Chat-Generative Pre-Trained Transformer (ChatGPT) when faced with diverse queries and prompts. It also places a strong emphasis on assessing the accuracy or correctness of ChatGPT’s answers. Methodology: The research will employ an online questionnaire designed to collect and analyze information. This survey, comprising 10 periodontology-related questions, will be sent to 30 periodontists. Each question will be presented individually to ChatGPT-3.5 using the new chat option, and the resulting responses will be systematically recorded in an Excel spreadsheet. Expert evaluation of ChatGPT-3.5’s responses will be conducted by a specialist in the field of periodontology. The assessment will employ a three-point Likert scale. Results: ChatGPT provided valuable assistance in answering periodontology-related questions with a high degree of accuracy, demonstrating its potential as a useful tool. Conclusion: The study concludes that ChatGPT holds promise as a reliable resource for providing accurate information in the field of periodontology, benefiting both practitioners and researchers.